A Review on the Advantages of Home Garden for Khmer People in Rural Areas of Cambodia - Roeurn Chivon; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
Homesteading, also known as home gardens, is a long-standing food production practice worldwide. It involves cultivating vegetables around the home, with some families growing multiple varieties without proper management. The aim of this study is to express how important of home garden is for individual Khmer families and livelihood in Rural areas of Cambodia. Home gardens therefore feature species that are complementary to one another and are characterized by cheap capital input and basic technology. They can improve the variety of foods in a home, provide fresh vegetables, save money by not buying vegetables, and increase income by selling extra vegetables to neighbors and friends. This income can be used to pay for other foods, school fees, and other expenses. Gardening also helps families exercise and stay fit, diversifying their diet, and reducing daily expenses. It also provides livelihood opportunities for resource-poor families and delivers various ecosystem services. In conclusion, working in the garden encourages family exercise and fitness, raising the diet's level of diversity even more, lower daily costs, such as providing resource-poor families with a means of subsistence, and provide several ecosystem services.